PERUVIAN COUNTABLE HISTORY: A BASIC LATIN AMERICAN PIECE OF CONTEXT - Rico Bonilla, Carlos Orlando (2013)
This project is been part of an important investigation about the evolution of the Peruvian countable practices. If we see that the studies have been a considered development there is still a potential margin of exploration and more to be realized. The same is been materialize in a big amount of primaries and secondary’s sources that are waiting to be examined and interpreted in detail that’s why the countable history in this country is a central piece of a puzzle in the interpretation and understanding of the past from the discipline and professional from the Latin American context.